Literature Review on Factors Affecting Medication Adherence in Tuberculosis Patients - Kustiawati, Ai; Permana, Iwan; Sanjaya, Waqid (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Introduction: With high death rates, tuberculosis (TB) is still a major worldwide health concern, especially in developing nations like Indonesia. Patient adherence to anti-tuberculosis medicine (OAT) for a minimum of six months has a significant impact on the efficacy of TB treatment. Treatment resistance, illness recurrence, and treatment failure can result from non-adherence. This study attempts to determine the internal and environmental variables that affect TB patients' medication adherence through a review of the literature. Methods: Article searches were conducted through Google Scholar, ScienceDirect, Garuda, and DOAJ for the years 2022-2026. The keywords used were tuberculosis and medication adherence, internal and external factors. There were 13 articles that met the inclusion criteria. Results and Discussion: All of these publications' findings show that medicine adherence is strongly correlated with internal characteristics such as knowledge, motivation, self-efficacy, attitude, resilience, and trust. Patient adherence is also influenced by external variables, including pharmaceutical side effects, stigma, access to healthcare services, the role of medication supervisors (PMOs), family support, and social support. Conclusion: Based on the results of the literature review, medication adherence in tuberculosis patients is influenced by both internal and external factors, so comprehensive interventions involving family and healthcare workers are needed to improve the effectiveness of treatment.